Monkeypox; Another global health emergency looming in the horizon - Fatima Shakeel Ahmed; Areeba Mateen; Ekta Kumari (Journal of the Pakistan Medical Association, 2023)
After the uproar caused by the COVID-19 pandemic, non-endemic countries like Pakistan are yet to face the danger of monkeypox, a virus of the Orthopox genus from the Poxviridae family, spread via animal-to-human and human-to-human transmission. Currently, two genetic clades of the virus have been identified within Africa. This disease is self-limiting with an incubation period of 5-21 days and is divided into two phases, with fever and prominent lymphadenopathy dominating the first phase and a skin rash with the propensity for the face and extremities being the main feature of the second phase. The disease has been rendered similar to small pox in presentation, though less contagious. Hence, the smallpox vaccine has proven to be 85% beneficial against monkeypox. With the first human case recorded in Congo in 1970, monkeypox was originally endemic to the African region.1 However, a surge in cases has now been reported in 50 countries in five World Health Organization regions, including non-endemic countries. 2 On 21st July 2022, the WHO declared monkeypox as a Global Health Emergency and issued recommendations to different groups of State Parties, considering their epidemiology and prevalence of disease. State parties with no confirmed cases of monkeypox are advised to strengthen their means to combat the disease. It is also recommended to plan, carry out epidemiological disease surveillance, and corroborate the availability of accurate and affordable diagnostic tests. The necessity for a plan to break stigmas against affected individuals, raise awareness in high-risk groups like transgender people, and encourage voluntary self-reporting and care seeking behaviour was highlighted. The temporary recommendations also elaborated on the need to train health workers from various fields to detect the disease early. Any probable or confirmed case of monkeypox is to be immediately reported to the WHO through established channels.3 Although, there have been no cases reported in Pakistan as of 26th July 2022, the slowly rising incidence in neighboring countries and India being the first to report a case of this region this month puts Pakistan at an immense risk.4 It is safe to assume that the advent of this disease into a resource-poor country may very well beset the country’s frail healthcare system. With the WHO declaring another global healthcare emergency, the need to implement timely and specific healthcare measures by developing states has now become imperative more than ever.3